Pengembangan Kemandirian Anak Usia 5-6 Tahun Di Tk Dharmawanita Tunas Harapan - Silranti, Malia; Yaswinda, Yaswinda (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2019)
Abstract: This study was aimed at describing development of the independence of children aged 5-6 year in TK Dharmawanita Tunas Harapan kindergarten in South. The research method is used a qualitative descriptive. The data were gained through conducting interviews, observation and documentation. The data were then analyzed using interactive model of data analysis from Miles and Huberman. The data was analyzed by using triangulation technique through collection data, reduction, display, and verification. The result of the study generally indicate that the development of independence in the Dharmawanita Tunas Harapan kindergarten in South Coastal district has been well implemente. But in planning it is not clearly described the development of children’s independence. Learning methods that are used by teachers in the development of independence are methods of habituation, conversation, question and Answer, playing, and giving assingment.